Soil quality and ecological benefits assessment of alpine desertified grassland following different ecological restoration measures - Li, Yiran; Hu, Sijia; Lang, Shanxin; Pu, Yulin; Zhang, Shirong; Li, Ting; Xu, Xiaoxun; Jia, Yongxia; Wang, Guiyin; Yuan, Dagang; Li, Yun (Frontiers in Plant Science, 2023)
Soil quality plays an irreplaceable role in plant growth for restored grassland.However, few studies investigate the comprehensive effects considering soil and vegetation properties during the restoration of desertified grassland, which restrict the virtuous circle of restored grassland ecosystem. By setting three restoration patterns of enclosure plus grass (EG), enclosure intercropping shrub-grass (ESG), and enclosure plus sand-barrier and shrub-grass (ESSG) with three different restoration years (≤ 5, 7-9, and ≥ 15 years), we selected twentyeight physicochemical and microbial indicators, and constructed a minimum data set (MDS) to analyze the influences of restoration measurements on soil quality and ecological benefits in alpine desertified grassland. The results showed that the MDS comprised seven soil quality indicators: silt, total nitrogen (TN), carbon-nitrogen ratio (C/N), total potassium (TK), microbial biomass carbon (MBC), microbial biomass phosphorus (MBP), and fungi. Soil quality index (SQI) and ecological restoration effect index (EREI) in restored grasslands significantly increased by 144.83-561.24% and 87.21-422.12%, respectively, compared with unrestored grassland, and their positive effects increased with extending restoration years. The increasing effects of SQI and EREI were the highest in ESSG, followed by EG and ESG. The increasing rate of SQI began to decrease after 5 years in EG and ESG, while it decreased after 7-9 years in ESSG, and that of EREI in EG was lower than ESSG in each restoration year. Our work revealed that ESSG was the optimum restoration pattern for desertified grassland, and anthropogenic monitoring and management measurements such as applying organic fertilization and mowing return reasonably should be carried out at the beginning of 5-year in EG and ESG as well as 7-year in ESSG to maintain sustainable ecological benefits. The study highlights that soil quality including microbial properties is a key factor for evaluating the 4 restoration effects of desertified grassland.